The essential works of Thomas More - More, Thomas, Saint, 1478-1535 (Yale University Press, 2020)
"The first comprehensive one-volume collection of St.Thomas More's writing In this book, Wegemer and Smith assemble More's most important English and Latin works for the first time in a single volume. This volume reveals the breadth of More's writing and includes a comprehensive selection of his works on theology, political philosophy, and law, as well as his poetry and prose. It provides the most complete picture of More's work available and will serve as a major, foundational resource for early modern scholars, teachers, and students."--Publisher.